AUDIT MANAJEMEN ATAS FUNGSI AKUNTANSI PADA PT. PARADOR PROPERTY MANAGEMENT - Dirvi Surya Abbas; Ananta Pasya Octaviani; Zachrasari Laksono; Galuh Putri Maharani; Diva Septy Annisa; Marisa Harahap; Anindya Ramadhani; Rima Dwi Amanda; Pingkan Pramudita Putri (Pascasarjana Universitas Sultan Ageng Tirtayas, 2025)
This study examines the implementation of management audit on the accounting function at PT Parador Property Management. Large companies require effective management to ensure operational continuity and sustainability. Accounting plays a strategic role by providing accurate and relevant information to support decision-making. However, despite established standards, accounting functions may not always operate efficiently and effectively, necessitating management audit. This research aims to identify strengths and weaknesses in PT Parador Property Management’s accounting system and provide recommendations for improvement. Data were collected through a case study using field research (interviews and questionnaires), library research (documents and literature), and online research (journals and reports). Findings indicate that the company has a clear organizational structure with well-defined job descriptions, detailed operational procedures, regular verification of assets and liabilities, accurate cash transaction recording, and timely financial reporting. Employee training enhances performance, yet the absence of periodic rotation in the finance department poses risks such as limited skill development, decreased motivation, and potential fraud. The study highlights the importance of management audit as a control instrument to optimize accounting functions and support sustainable business operations, providing insights for companies and researchers in the property sector